Effects of Recombinant Spidroin rS1/9 on Brain Neural Progenitors After Photothrombosis-Induced Ischemia - Moisenovich, Mikhail M.; Silachev, Denis N.; Moysenovich, Anastasia M.; Arkhipova, Anastasia Yu.; Shaitan, Konstantin V.; Bogush, Vladimir G.; Debabov, Vladimir G.; Latanov, Alexander V.; Pevzner, Irina B.; Zorova, Ljubava D.; Babenko, Valentina A.; Plotnikov, Egor Y.; et al. (Frontiers in Cell and Developmental Biology, 2020)
The existence of niches of stem cells residence in the ventricular-subventricular zone and the subgranular zone in the adult brain is well-known. These zones are the sites of restoration of brain function after injury. Bioengineered scaffolds introduced in the damaged loci were shown to support neurogenesis to the injury area, thus representing a strategy to treat acute neurodegeneration. In this study, we explored the neuroprotective activity of the recombinant analog of Nephila clavipes spidroin 1 rS1/9 after its introduction into the ischemia-damaged brain. We used nestin-GFP transgenic reporter mouse line, in which neural stem/progenitor cells are easily visualized and quantified by the expression of green fluorescent protein (GFP), to determine the alterations in the dentate gyrus (DG) after focal ischemia in the prefrontal cortex. Changes in the proliferation of neural stem/progenitor cells during the first weeks following photothrombosis-induced brain ischemia and in vitro effects of spidroin rS1/9 in rat primary neuronal cultures were the subject of the study. The introduction of microparticles of the recombinant protein rS1/9 into the area of ischemic damage to the prefrontal cortex leads to a higher proliferation rate and increased survival of progenitor cells in the DG of the hippocampus, which functions as a niche of brain stem cells located at a distance from the injury zone. rS1/9 also increased the levels of a mitochondrial probe in DG cells, which may report on either an increased number of mitochondria and/or of the mitochondrial membrane potential in progenitor cells. Apparently, the stimulation of progenitor cells was caused by formed biologically active products stemming from rS1/9 biodegradation, which can also have an effect upon the growth of primary cortical neurons, their adhesion, neurite growth, and the formation of a neuronal network. The high biological activity of rS1/9 suggests it as an excellent material for therapeutic usage aimed at enhancing brain plasticity by interacting with stem cell niches. Substances formed from rS1/9 can also be used to enhance primary neuroprotection, resulting in reduced cell death in the injury area.